1998
DOI: 10.1038/bjc.1998.498
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations and human papillomavirus DNA in oral squamous cell carcinoma: correlation with apoptosis

Abstract: Summary Forty-two oral squamous cell carcinomas (SCCs) were analysed for p53 mutations and human papillomavirus (HPV) (Regezi et al. 1993). W'hereas the epidemiology has been w-ell described so far. the molecular steps involsed in the pathogenesis of these common neoplasms are poorly understood. The role of human papillomas-irus (HPV) in the development of anogenital cancers has been widely studied. and current evidence shows that HPV infection is necessars for the desvelopment of most cervical cancers (zur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
3
16
0
3
Order By: Relevance
“…Therefore, the high percentage of HPV positivity of the control tissues in the present study is not unusual. Our finding of no correlation between AI and HPV was also in agreement with the results of Isacson et al [4] and Koh et al [20]. We have previously identified ABs in exfoliated cervicovaginal epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the high percentage of HPV positivity of the control tissues in the present study is not unusual. Our finding of no correlation between AI and HPV was also in agreement with the results of Isacson et al [4] and Koh et al [20]. We have previously identified ABs in exfoliated cervicovaginal epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…Although the E6 oncoprotein of HPV is implicated in the functional inactivation of p53 (a gene that regulates apop- tosis) [18], in two separate studies [4,19], however, the AI was not found to be correlated with HPV infection. Koh et al [20] suggested that the decrease in apoptosis is more closely related to p53 mutation rather than HPV infection. In the present study, the AI was also not found to be affected by HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the method is risky to overlook mutations in case wt-p53 sequences of contaminating regular cells disturb the signal of the mutated cells. In studies reporting higher mutation rates single-strand conformation polymorphism (SSCP) was applied, a technique which has shown rather frequent false positive results (1).…”
Section: Discussionmentioning
confidence: 99%
“…More than 90% of these represent squamous cell carcinomas (HNSCC) (1). The main risk factors for developing HNSCC are the carcinogenic substances of tobacco smoke and alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that the association between HPV infection and/ or p53 inactivation and the risk of oral cancer is implicated, although it is not a mutually exclusive event (69,70). Immunohistochemical detection of p53 protein clarified that HPV and p53 protein alteration coexisted in oral lesions, and p53 mutation was initiated during early events of HPV infection to lead to oral cancer (71).…”
Section: Hpv In Oral Lesionsmentioning
confidence: 99%